Key Determinants of Acceptance and Use of E-Services Based on Marketing Technology Process - Metasari, Rosy Anresia; Sujarwoto, Sujarwoto (Jurnal Ilmiah Administrasi Publik, 2019)
Nowadays, government uses e-services to boost the services for citizen with many endeavours but there are some e-service where the technology did not accommodate or appropriate to citizen needs. In order to improve the service and accomodate the citizen needs, this journal attempts to explore the related key determinants or variables. Exploration of theory is begun from the definition of e-services, the explanation of public choice theory and organizational behaviour theory in public administration until the model of citizen use and acceptance of e-services. Considering the government efforts to introduce the e-services, this model combines Unified Theory of Acceptance and Use of Technology (UTAUT) with the marketing process to seek key determinants from citizen personality, perceptions, and attitude.